Kinetic study of palm oil and soya bean oil mixtures/ Zaliha Omar - Omar, Zaliha (2000)
Palm oil consists mainly of triacylglycerols of palmitic and oleic acids. It is a semisolid at room temperature and can be separated into two fractions, i.e. a solid fraction (stearin) and a liquid fraction (olein) by fractionation process at a controlled temperature. The stearin fraction is a co-product of olein production and is a cheaper fraction. However, with the slip melting point in the range of 46-50°C, and it is a highly saturated fat, only 10% is used as a very useful source of natural hard component in the manufacture of edible fat such as margarine, shortenings, vanaspati etc. Considerable potential in the usage of palm stearin in the edible food industry exists if the physical and chemical properties of palm stearin can be modified. In this study the palm oil, soft and hard stearins were blended with 100% pure highly unsaturated soya bean oil at different ratios. The slip melting point (SMP), iodine value (IV), solid fat content (%SFC) by Pulsed Nuclear Magnetic Resonance, and fatty acids composition by Gas Chromatography of the blends were determined. These data then used for the crystallization study based on the thermal behaviour by Differential Scanning Calorimeter, crystal morphological by using polarized microscope and crystal polymorphic forms by X-ray diffractometer. The three basic polymorphic forms a, p and p1 exhibit distinct properties being largely dependent on the crystallization conditions. With the understanding of the behaviours of these blends, it hoped that the usage of palm oil, especially the stearins could be increased and diversified.